1994
DOI: 10.1093/bja/73.6.786
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative throat complaints after tracheal intubation

Abstract: We have investigated the incidence of throat complaints 6-24 h after tracheal intubation in 1325 patients. Variables such as anaesthetic drug, intubation time, number of intubation attempts, gastric tube, sex and age were recorded. The incidence of sore throat was considerably lower (14.4%) compared with other reports in the literature and was significantly greater in females (17.0% vs 9.0%) and after thyroid surgery. The incidence of sore throat was not increased after multiple intubation attempts or after ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
164
6
8

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(190 citation statements)
references
References 14 publications
12
164
6
8
Order By: Relevance
“…22 This factor may also explain our somewhat lower incidence of postoperative laryngeal symptoms, recorded 24 hr after anesthesia, than reported by Combes et al, 6 although female gender, gynecological surgery, and duration of intubation are well known risk factors for complaints of laryngeal symptoms after anesthesia. 2,3 Finally, the selected doses of remifentanil and propofol ensured acceptable intubating conditions in more than 95% of patients. However, within acceptable conditions, the distribution of excellent and good conditions was unequal in the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…22 This factor may also explain our somewhat lower incidence of postoperative laryngeal symptoms, recorded 24 hr after anesthesia, than reported by Combes et al, 6 although female gender, gynecological surgery, and duration of intubation are well known risk factors for complaints of laryngeal symptoms after anesthesia. 2,3 Finally, the selected doses of remifentanil and propofol ensured acceptable intubating conditions in more than 95% of patients. However, within acceptable conditions, the distribution of excellent and good conditions was unequal in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…First, since the primary outcome of our study was the incidence of SLI, use of a depolarizing agent was avoided, because the role of succinylcholine in the etiology of postoperative sore throat and hoarseness remains unclear. 2,3,23 Second, cisatracurium is reported to produce less histamine release and fewer allergic reactions compared to other nondepolarizing NMBDs, such as rocuronium, 7,24 even though reports of anaphylactic reactions after cisatracurium administration were published since its introduction into clinical anesthesia. 7 The mean onset of action of cisatracurium was > six minutes, inducing a mean delay of three minutes of the first attempt to intubate the trachea compared to the patients in group Placebo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, such pressure trauma is not necessarily associated with sore throat, a common if usually minor complication of tracheal intubation. Sore throat has been associated with younger patients undergoing short procedures [5]; Christensen et al found no association with length of procedure and a 50% incidence of hoarseness after intubation [6]. An explanation for this may be that trauma arises during the process of intubation and not only from the presence of a tracheal tube.…”
mentioning
confidence: 99%